HLA Class II Differentiates Between Thyroid and Polyglandular Autoimmunity - Barkia Beradhi, S.; Flesch, B. K.; Hansen, M. P.; Matheis, N.; Kahaly, G. J. (Hormone and Metabolic Research, 2016)
The HLA class II genes are susceptibility genes for autoimmune endocrine diseases; however, scarce data are available pertaining to the determinants of genetic susceptibility to polyglandular autoimmunity (PGA). A total of 300 consecutive and unselected patients with either PGA or monoglandular autoimmune thyroid disease (AITD) and 100 healthy control subjects were genotyped for the HLA class II DRB1, -DQA1, and -DQB1 alleles. Compared to patients with AITD and controls, the HLA-DRB1*03 (pc=0.001), *04 (pc<0.001), -DQA1*03 (pc<0.001), and -DQB1*02 (pc=0.001) alleles were increased in patients with PGA. When dividing patients with Hashimoto’s thyroiditis (HT) into those with PGA (PGA-HT) vs. those with HT as monoglandular disease, significant differences for the DRB1*03 (pc=0.001) and DQA1*03 (pc=0.001) alleles were observed. In contrast, the DQB1*02 allele was more prevalent in PGA patients with Graves’ disease (PGA-GD) vs. those with monoglandular GD (pc=0.002). The HLA-DRB1*15 (pc=0.001), -DQA1*01 (pc=0.001), -DQB1*05 (pc=0.002) and -DQB1*06 (pc=0.002) alleles were significantly less present in PGA compared to monoglandular AITD and controls, thus indicating protective alleles. The HLA class II alleles differentiate between mono- and polyglandular autoimmunity in patients with autoimmune thyroid disease.
Keywords: polyglandular autoimmunity; immunogenetics; HLA class II alleles; autoimmune thyroid disease